DETERMINANTS OF BANK LIQUIDITY IN SYRIA: A COMPARATIVE STUDY BETWEEN ISLAMIC AND CONVENTIONAL BANKS - Khaled Nour Aldeen; Eko Siswahto; Sri Herianingrum; Ziad Mhmmd Wafik Al Agawany (International Journal of Accounting, Finance and Business, 2020)
Most of the studies have excluded Syrian banks from their samples due to the violent conflict in the country, which will affect their results. The main objective of this research is to evaluate liquidity risk through a comparative analysis between Islamic and conventional banks of Syria. We employed paired sampled t-test and regression with OLS estimation. Secondary data were collected spanning 2011-2017, for the entire private banking sector in Syria. This study investigates the significance of size of the bank and several financial ratios on the banks’ liquidity. Our finding manifested that an insignificant difference exists between Islamic and conventional banks in terms of liquidity. Furthermore, Islamic banks liquidity risk management predictors were significant and nonperforming finance ratio (NPF) and bank size at 10% level. Whereas in its counterparts all the variables selected in our model were significant predictors at 5%. Our results show different factors in different significant level affect liquidity risk in each bank. This study provides an alluded picture about Syrian private banking sectors, particularly liquidity risk management. Which might help the authorities to set future prospects.